THE INFLUENCE OF REWARD AND PUNISHMENT ON EMPLOYEE PERFORMANCE - Trisyanto, Bobi; Bayu Maulana, Muhammad; Najiha, Juzi (Cirebon International Conference on Education and Economics Proceeding, 2024)
The purpose of this research is to investigate the impact of various forms of motivation on employee performance in the spiritus & alcohol factory setting. In particular, this study will examine the following questions: (1) the effect of reward on employee performance in spiritus & alcohol factory (2) the effect of punishment on employee performance in spiritus & alcohol factory (3) the simultaneous effect of reward and punishment on employee performance in spiritus & alcohol factory. This study employs an associative research approach, employing quantitative methods. The population of this study comprised all employees of the spiritus & alcohol factory, with a sample size of 75 respondents. Sampling was conducted using saturated samples as the sampling technique. A questionnaire was employed as the data collection technique. The Assumption Test employs normality testing and multicollinearity testing. The Regression Test utilizes multiple regression testing. The coefficient of determination test is utilized to ascertain the percentage of dependent change (Y) attributed to the independent variable (X). Hypothesis testing is conducted using the T and F test. The results of this study concluded that: (1) reward had a significant effect on the performance of employees which indicated the value of tcount <ttable ie 3,212 > 1.993. (2) punishment has a significant effect on employee performance which is indicated by tcount <ttable, namely 4,605 > 1.993. (3) reward and punishment simultaneously effects on employee performance which is indicated by the value of Fcount> Ftablethat is 22,238 >3.12.